2010
DOI: 10.2146/ajhp090588
|View full text |Cite|
|
Sign up to set email alerts
|

Continuous quality improvement using intelligent infusion pump data analysis

Abstract: Compliance rates for use of infusion pump safety software varied among CCAs over time. Education, auditing, and refinement of drug libraries led to improved compliance in most CCAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
35
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 6 publications
1
35
4
Order By: Relevance
“…5,6,10 Case study and qualitative research evidences have begun to confirm what clinicians have long known: end users bypass safety features or inappropriately override alerts on smart pumps. 11,12 For example, in a qualitative study from 2007, McAlearney and colleagues 5 found that nurses responded to numerous practical challenges when using smart infusion pumps by deliberately improvising steps within the intravenous (IV) medication delivery process and bypassing various safety features. Such improvisations are often referred to as work arounds, which have been defined in the literature as "… informal, temporary practices for handling exceptions to the normal workflow."…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5,6,10 Case study and qualitative research evidences have begun to confirm what clinicians have long known: end users bypass safety features or inappropriately override alerts on smart pumps. 11,12 For example, in a qualitative study from 2007, McAlearney and colleagues 5 found that nurses responded to numerous practical challenges when using smart infusion pumps by deliberately improvising steps within the intravenous (IV) medication delivery process and bypassing various safety features. Such improvisations are often referred to as work arounds, which have been defined in the literature as "… informal, temporary practices for handling exceptions to the normal workflow."…”
mentioning
confidence: 99%
“…14,15 Despite the widespread adoption of smart pump technology, its benefits have not been fully realized, and ensuring institutionwide compliance has proven challenging. 11,12 Health care professionals acknowledge that many of these challenges are not technical but instead organizational, cultural, and psychological in nature. 16 To date, much of the literature regarding smart pump use comes from engineering and clinical perspectives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This decreased error rate also has been associated with cost savings, workflow improvement, and legal risk reduction. [2][3][4] Through the use of IV infusion pumps equipped with safety software (''smart'' or ''intelligent'' infusion pumps), many high-risk medications can be administered safely. There is evidence that by integrating IV infusion pumps with institutional information systems (eg, electronic medical records, barcode point-of-care, and computerized physician order entry), evidence-based standards could be applied to patient care, thereby increasing patient safety.…”
mentioning
confidence: 99%
“…[2][3][4]7 The Association for the Advancement of Medical Instrumentation (AAMI) has released a list of actions that hospitals can take to immediately improve medication infusion safety. These actions include ensuring that wireless capability is an essential requirement in purchasing decisions, maximizing the use of smart-pump features and capabilities, and analyzing and using the continuous quality improvement data generated by these infusion systems.…”
mentioning
confidence: 99%